Analisis Pelaksanaan Pembelajaran Daring Pada Anak Berkebutuhan Khusus dan Siswa Reguler di SDN 007 Sungai Pinang - Samsul Adianto (SISTEMA: Jurnal Pendidikan, 2023)
A b s t r a c t This research was motivated by the COVID-19 pandemic which made all activities carried out from home, including learning and teaching activities. Therefore, this study aims to find out how the implementation of online learning for children with special needs and regular students at SDN 007 Sungai Pinang for the 2020/2021 learning year. The results of research on children with special needs without using applications and teachers only give papers to parents containing a collection of questions that must be done by students, so online learning that runs is considered to still experience many obstacles. Obstacles that occur for example such as not having regular and scheduled meetings between teachers and students, students do not want to learn because they do not meet with their teachers directly, parents who do not know how to handle their children well so that learning does not go well. While the implementation of online learning for regular students takes place with the help of a messaging application called WhatsApp. In this application, teachers send questions to students directly in the group they have created so that teachers and students have a regular and scheduled meeting schedule. In addition, there are new things such as teachers conducting video call activities with each student to find out how their students are progressing in writing, counting and reading. Therefore, online learning for regular students is considered to have gone well. Keywords: ABK and Regular Students